"To print her discourses & hymmes": the typographic features of Anna Trapnel's prophecies. Issue 2 (4th March 2021) - McGann, Claire
ABSTRACT: This article discusses Anna Trapnel's final publication: a 990-page volume of prophetic verse printed in around 1659, which now survives in a single copy held by the Bodleian Library. Advocating the value of attending to the materiality of early modern women's texts, this article examines the semantic significance of the typography in this large volume of prophecies. First, I argue that the work's distinctive letter forms and ornamental headers may affiliate it with the printing house of James Cottrell. Second, these specific visual motifs are explored as indicators of Trapnel's broader religious and textual community in mid-seventeenth century England. Finally, the article suggests ways in which we might read the volume's typographic features as both supportive, and subtly undermining, of Trapnel's highly charged religious discourse.